Penggunaan Media Pembelajaran Video Animasi Powtoon Siswa SMA Al-Azhar 3 Bandar Lampung - Lusi Septiana; Sumadi Sumadi; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2020)
The aims of this study was to find out the effect of using the Powtoon animation video learning media on the interests and learning outcomes of students geography at Al-Azhar 3 High School Bandar Lampung. The research method was a quasi-experimental type of non-equivalent control group design with a population of 88 students of Class XI IIS Al-Azhar 3 High School by using a purposive sampling technique. The research sample consisted of 60 students. The instruments were 20 pretest and posttest questions and 30 questionnaire statements. Simply linier regression test and t-test were used to analyze the data, the overall results t count is greater than t table and significance less than 0.05. It can be concluded that there was influence of the use of Powtoon animation video learning media on learning interests and results, and there were differences in classroom learning outcomes using Powtoon animation video learning media and classes that did not use learning media.Tujuan penelitian adalah mengetahui pengaruh penggunaan media pembelajaran video animasi Powtoon terhadap minat dan hasil belajar geografi siswa SMA Al-Azhar 3 Bandar Lampung. Metode penelitian yaitu quasi experimental tipe non-equivalent control grup design dengan populasi 88 siswa kelas XI IIS SMA Al-Azhar 3 menggunakan teknik purposive sampling. Sampel penelitian berjumlah 60 siswa. Instrumen yang digunakan 20 soal pretest dan posttest dan 30 pernyataan angket. Teknik analisis uji regresi linier sederhana dan uji t digunakan untuk analisis data, hasil seluruhnya t hitung lebih besar dari t tabel dan signifikansi kurang dari 0,05. Dapat disimpulkan bahwa terdapat pengaruh penggunaan media pembelajaran video animasi Powtoon terhadap minat dan hasil belajar, dan terdapat perbedaan hasil belajar kelas penggunaan media pembelajaran video animasi Powtoon dan kelas yang tidak menggunakan media pembelajaran.Kata kunci: hasil belajar, media pembelajaran, minat belajar